Physical and mechanical properties of permeable concrete with aggregates of porcelain electrical insulator residues (Research, Society and Development, 2021)
The present work aims to study the influence of the use of waste porcelain electrical insulators on the properties of permeable concrete. In recent years, several researches have been developed with the objective of reducing the environmental impacts of industrial waste, adjusting systems so that the waste from a production process can be used as raw material for the production of other products. The electric energy producing companies produce an estimated annual liability of 25,000 ton / year of porcelain electrical insulators, resulting from the replacement of outdated parts and industrial quality control, and currently do not have a disseminated procedure regarding the reuse of this ceramic, often being improperly discarded in the environment. Specifically, the civil construction sector presents itself as a sector that can incorporate these waste porcelain electrical insulators into its production. The concretes were tested for compressive strength at the ages of 14 and 28 days, with the respective percentages of replacing the volume of conventional coarse aggregate with 10% and 30% porcelain electrical insulator waste. The results show that the compressive strength increased with the increase in the percentage of waste insulators, the material under study resented a permeability coefficient that meets a very low degree of permeability and the void index did not present characteristics of permeable concretes. The samples produced did not meet the normative requirement (NBR 16416-table 8) of compressive strength of 20-35 MPa.